Gatekeeping Process of LGBT News in Republika Online - Molasiarani S., Klaudia; Lukmantoro, S.Sos, M.Si, Triyono (Interaksi Online, 2016)
Mass media nowadays fight for the values, interest, and ideology through their reporting. In that case, all of the fact that is found by the journalist will pass the selection process in some steps to form a news that is worth to be published. For sure, it also happens in the process of LGBT news production in Republika Online. It makes the news tend to be unbalance and show the discriminatory to the group of LGBT. This research uses the theory of gatekeeping with descriptive qualitative method and critical paradigm. The data of this research was taken by interviewing some editorial crew involving in news production of LGBT, such as reporter, assistant of managing editor, and deputy of managing editor. The result of this research shows that in the individual level, both reporter and editor have their own values of interpreting LGBT phenomenon. As a gatekeeper, they use their own values to construct the reality. Some argue that the behaviour of LGBT is a kind of rights, but the others argue that their behaviour is not appropriate with the value that is constructed in the society. However, that diversity of ideas change into the same one because of the media routines. For sure, the media routines have some norms and regulation of reporting and directing the news angle to make a public opinion. And so, it limits the diversity of ideas owned by each reporter. Republika Online argue that LGBT is a deviant behaviour as it contradict with the value bringing by the society. Because of that, this media need to fight for the value that used to exist in society. Further, the editors as a gatekeeper in this level have an authority to edit the news written by reporter. So, it is very possible if the personal values bringing by reporter on their article are reduced. The attitude of Republika Online which is tend to be impartial to the group of LGBT is close to the vision and mision of this organization. It is a kind of guidance for the media worker in production news, especially LGBT news. Based on that guidance, Republika also try to fight for the interest of communities by voicing the Moslem’s values. Beside that, Republika Online also try to seek for legitimation of their attitude in reporting LGBT by selecting the source of information. It means, Republika Online try to give a space for them who defend for the rights and freedom of LGBT (cover both sides). But, the dominant part in the reporting focus on the sources of information that contradict with LGBT groups. The ratio space of people who contradict and defend is 70 : 30. It makes the news become bias of cover both sides. The last level of gatekeeping process is social system level. In this level, the dominant culture is assumsed that it refusing the behaviour of LGBT. That point of view seems to strength the Republika Online’s attitude to give a bad justification to LGBT. So, the dominant level of gatekeeping process of LGBT news in Republika Online is organization level.